Interactive Learning Innovation: Training Critical Thinking through a Modified Mafia Game at SMK PGRI 6 Malang - Mardhiyatillah, Nahdiyanna; Sukma, Salsabila Melati; Multisari, Widya; Bahtiar, Ahmad (Universitas Negeri Malang, 2024)
Instructional media serve as a means of communication in print or audiovisual form. This has also been evidenced in the results of interviews and observations conducted by the researchers, which show that students feel bored and appear passive when learning using PowerPoint presentations or lectures. Hence, one of the solutions offered by the researchers is to use game media. One of the games that can be used as a medium to train critical thinking is the Mafia game. This research aims to develop a prototype medium by modifying the Mafia game to enhance students' critical thinking, making the teaching and learning process both beneficial and enjoyable. This research is a development study employing the Research and Development (R&D) method. The process of creating the Mafia game media involves several stages of research and development following the Borg & Gall (1983) model. The research began with a needs analysis of the instructional media used by teachers. In the planning stage, activities included compiling materials and designing game cards. In the product development stage, the researchers printed a total of 30 game cards (4 Mafia, 3 Doctor, and 23 Citizen). Future recommendations from this research and development include testing the product's accessibility with potential users.